Revitalizing Positive Behavior through the Dolanan Village Concept: An Alternative for Early Childhood Socio-emotional Development in the Alpha Generation Era - Yusuf, Muhammad; Utama, Ferdian; Rachmad, Yoesoep Edhie (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2025)
The Generation Alpha era marked by the dominance of digital technology has had a significant impact on the socio-emotional development of early childhood. Excessive exposure to technology often reduces children's direct social interactions, thus inhibiting their ability to develop social and emotional skills. This study aims to explore the concept of Kampung Dolanan as an alternative to revitalize positive behavior in early childhood through traditional games. Using a qualitative approach and case study design, the study was conducted in Metro City, Lampung. Data were obtained through participatory observation, interviews with parents, educators, and facilitators, and document analysis. The results of the study indicate that Kampung Dolanan is able to support children's socio-emotional development by improving cooperation skills, empathy, emotional management, and self-confidence. Traditional games that are implemented in a structured manner not only preserve local culture but also provide space for children to learn social values in a supportive environment. The active role of parents, educators, the community, and local government is very important in the successful implementation of the Kampung Dolanan concept. This study recommends Kampung Dolanan as an innovative socio-emotional development model to support the growth and development of early childhood in the digital era.